Thrombocytopenia in Dengue Hemorrhagic Fever - Sunarto Sunarto; Sutaryo Sutaryo (Indonesian Pediatric Society, 1992)
According to WHO thrombocytopenia is one of the diagnostic criteria of DHF. On the other hand many studies have reported DHF cases without evidence of thrombocytopenia. One hundred fifty nine DHF out of485 suspected cases were assessed for their platelet counts. Diagnosis of DHF was established based on the WHO criteria, and confirmed by the hemagglutination inhibition test. The platelet counts were done serially and intensively by phase contrast microscope from the first day of hospitalization until the patient's discharge. In 77 patients thrombocytopenia appeared for the first time during hospitalization. Mild thrombocytopenia appeared in almost all of these cases before thrombocyte count of 100,000 reached. Seventy two patients had shown thrombocytopenia on the day of admission. No thrombocytopenia was found on the second day of illness, the earliest time of the detection of thrombocytopenia was on the Jrri and the latest was on the 8th day of illness. Thrombocytopenia lasted 1-5 days. It is concluded that many DHF diagnosis would have been missed if the thrombocyte investigation had not been done serially and intensively. Mild thrombocytopenia in DHF suspected patients should call attention to do platelet investigation intensively in those cases.